Architectural analysis of root system and phytohormone biosynthetic genes expression in wheat (Triticum aestivum L.) inoculated with Penicillium oxalicum. (21st September 2022) - Tiwari, P.K.; Yadav, J.; Singh, A.K.; Srivastava, R.; Srivastava, A.K.; Sahu, P.K.; Srivastava, A.K.; Saxena, A.K.
Abstract: In this study, a fungal plant growth promoter Penicillium oxalicum T4 isolated from non‐rhizosphere soil of Arunachal Pradesh, India, was screened for different plant growth promoting traits in a gnotobiotic study. Though inoculation improved the overall growth of the plants, critical differences were observed in root architecture. Confocal Laser Scanning Microscope, Scanning electron microscope and the stereo microscopic study showed that inoculated wheat plants could develop profuse root hairs as compared to control. Root scanning indicated improvement in cumulative root length, root area, root volume, number of forks, links, crossings, and other parameters. A confocal scanning laser microscope indicated signs of endophytic colonization in wheat roots. Gene expression studies revealed that inoculation of T4 modulated the genes affecting root hair development. Significant differences were marked in the expression levels of TaRSL 4, TaEXPB 1, TaEXPB 23, PIN‐FORMED protein, kaurene oxidase, lipoxygenase, ACC synthase, ACC oxidase, 9‐cis‐epoxycarotenoid dioxygenase, and ABA 8′‐hydroxylase genes. These genes contribute to early plant development and ultimately to biomass accumulation and yield. The results suggested that P. oxalicum T4 has potential for growth promotion in wheat and perhaps also in other cereals. Abstract : Significance and Impact of the Study; Although the impact of microbes on plant growth promotion and root architecture has been widely examined using bacteria, the role of fungi is much less studied. Here, we examined the effect of a potential fungal plant growth promoter Penicillium oxalicum T4 on root architecture and growth of wheat seedlings. Confocal scanning laser micrographs and scanning electron micrographs indicted profuse colonization in wheat roots and induction of root hairs, respectively. Furthermore, P. oxalicum T4 was shown to modulate the expression of host genes related to root growth and development. Overall, P. oxalicum T4 was found to hold promise as a potential microbial formulation for boosting wheat growth.